The Teaching of Reading and Cognitive Mediation in Students of Academic Average: A Correlation Study - Arenas-Parada, Alba Luz (2021)
Objective. This scientific research article aims to determine the relationship between the ICT-supported reading process and the cognitive mediation of high school students. The cognitive mediation to which a student is exposed in their school development involves a series of factors such as intentionality, significance, and the feeling of competence that can be analyzed based on reading activity. Methodology. This research with a quantitative approach established the correlation between the ICT-supported reading process and cognitive mediation. A stratified sample with tenth- and eleventh-grade students from a public school was selected. The data were obtained from the application of a survey-type technique, developed in a questionnaire format instrument with a Likert scale. The data were submitted to an expert review, plus normality test, in SPSS, determining Pearson’s coefficient. Results. Statistical data revealed difficulties in fluency and the feeling of competence of cognitive mediation. Conclusions. It is possible to affirm that there is a low positive correlation between the ICT-supported reading process and intentionality, significance, and the feeling of competence.